Family Environment, Neurodevelopmental Risk, and the Environmental Influences on Child Health Outcomes (ECHO) Initiative: Looking Back and Moving Forward - Bush, Nicole R.; Wakschlag, Lauren S.; LeWinn, Kaja Z.; Hertz-Picciotto, Irva; Nozadi, Sara S.; Pieper, Sarah; Lewis, Johnnye; Biezonski, Dominik; Blair, Clancy; Deardorff, Julianna; Neiderhiser, Jenae M.; Leve, Leslie D.; et al. (Frontiers in Psychiatry, 2020)
The family environment, with all its complexity and diverse components, plays a critical role in shaping neurodevelopmental outcomes in children. Herein we review several domains of the family environment (family socioeconomic status, family composition and home environment, parenting behaviors and interaction styles, parental mental health and functioning, and parental substance use) and discuss how these domains influence neurodevelopment, with particular emphasis on mental health outcomes. We also highlight a new initiative launched by the National Institutes of Health, the Environmental influences on Child Health Outcomes (ECHO) program. We discuss the role that ECHO will play in advancing our understanding of the impact of the family environment on children’s risk for psychiatric outcomes. Lastly, we conclude with important unanswered questions and controversies in this area of research, highlighting how ECHO will contribute to resolving these gaps in our understanding, clarifying relationships between the family environment and children’s mental health.